Association Between 5-HTTLPR Polymorphism and Tics after Treatment with Methylphenidate in Korean Children with Attention-Deficit/Hyperactivity Disorder - Park, Seo Yeon (J Child Adolesc Psychopharmacol, 2015)
Objectives: The purpose of this study is to examine the relationship between 5-HTTLPR polymorphism (44-bp insertion/deletion polymorphism of serotonin transporter gene) and methylphenidate (MPH) treatment response, as well as the association between the adverse events of MPH treatment and 5-HTTLPR polymorphism in children with attention-deficit/hyperactivity disorder (ADHD). Methods: A total of 114 children with ADHD (mean age 9.08 ± 1.94 years) were recruited from the child psychiatric clinic in a hospital in South Korea. We have extracted the genomic DNA of the subjects from their blood lymphocytes and analyzed 5-HTTLPR polymorphism of the SLC6A4 gene. All children were treated with MPH for 8 weeks, with clinicians monitoring both the improvement of ADHD symptoms and the side effects. We compared the response to MPH treatment and adverse events among those with the genotype of 5-HRRLPR polymorphism. Results: There was no significant association between the 5-HTTLPR genotype and the response to MPH treatment in children with ADHD. Subjects with the S/L+L/L genotype tended to have tics and nail biting (respectively, p < 0.001, p = 0.017). Conclusions: The results of this study do not support the association between the 5-HTTLPR polymorphism and treatment response with MPH in ADHD. However, our findings suggest the association between 5-HTTLPR polymorphism and the occurrence of tics and nail-biting as an adverse event of methylphenidate. This may aid in our understanding of the genetic contribution and genetic susceptibility of a particular allele in those ADHD patients with tics or nail biting.